Anthropozoonotic endoparasites in free-ranging urban South American sea lions (Otaria flavescens) - Hermosilla, Carlos; Silva, Liliana M. R.; Navarro, Mauricio; Taubert, Anja; Justus Liebig University Giessen (My University, 2016)
The present study represents the first report on the gastrointestinal endoparasite fauna of a free-ranging urban colony of South American sea lions (Otaria flavescens) living within the city of Valdivia, Chile. A total of 40 individual faecal samples of South American sea lions were collected during the year 2012 within their natural habitat along the river Calle-Calle and in the local fish market of Valdivia. Coprological analyses applying sodium acetate acetic formalin methanol (SAF) technique, carbol fuchsin-stained faecal smears and Giardia/Cryptosporidium coproantigen ELISAs, revealed infections with 8 different parasites belonging to protozoan and metazoan taxa with some of them bearing anthropozoonotic potential. Thus, five of these parasites were zoonotic (Diphyllobothriidae gen. sp., Anisakidae gen. sp., Giardia, Cryptosporidium, and Balantidium). Overall, these parasitological findings included four new parasite records for Otaria flavescens, that is, Giardia, Cryptosporidium, Balantidium, and Otostrongylus. The current data serve as a baseline for future monitoring studies on anthropozoonotic parasites circulating in these marine mammals and their potential impact on public health.
Keywords: ddc:630